Analysis of the traits of deliberate substance abuse and its correlation with psychological states in adolescents - Liu, Xinhui; Wang, Zhihua; Liang, Hongyu; Qi, Xin; Wang, Lihua (Frontiers in Psychiatry, 2026)
BackgroundDeliberate substance abuse among adolescents represents a significant public health concern, yet comprehensive analysis of its characteristics and psychological correlates remains limited.ObjectiveTo analyze the characteristics of deliberate substance abuse among adolescents and its correlation with psychological states.MethodsThis retrospective cohort study included 158 adolescents (mean age: 12.87 ± 1.32 years; 123 girls, 35 boys) admitted for deliberate substance abuse between January 2020 and December 2022. Data were collected using standardized instruments including the Risky Behavior Questionnaire for Adolescents (RBQ-A), Center for Epidemiologic Studies Depression Scale (CES-D), Multidimensional Anxiety Scale for Children (MASC), Cognitive Emotion Regulation Questionnaire-Chinese Version (CERQ-C), Adolescent Self-Rating Life Events Checklist (ASLEC), and Adolescent Social Support Scale (ASSS).ResultsThe number of cases increased annually (2020: 34; 2021: 54; 2022: 70), with a higher prevalence among girls than boys. The most commonly abused substances were antipsychotic medications. Univariate analysis revealed significant associations between deliberate substance abuse and factors including presence of medical personnel in the family, family structure, guardian’s education background, residential area, sole child status, knowledge of pharmaceutical security, depression/anxiety, CERQ-C scores, adverse experiences, and social support (all P < 0.05). Appropriate correlation analyses revealed that psychological states were significantly correlated with these factors (all P < 0.05). Multivariate linear regression identified guardian’s education background, knowledge of pharmaceutical security, depression/anxiety, CERQ-C scores, and social support as the primary factors affecting psychological states (all P < 0.05).ConclusionDeliberate substance abuse among adolescents is associated with multiple sociodemographic and psychological factors. Interventions targeting modifiable factors such as drug safety education and social support may help prevent this behavior.